1985
DOI: 10.1136/pgmj.61.717.583
|View full text |Cite
|
Sign up to set email alerts
|

Ketanserin in essential hypertension: a double-blind, placebo-controlled study

Abstract: Summary:The antihypertensive effect of the selective serotonin antagonist ketanserin was examined in a double-blind, placebo-controlled, parallel group study in 20 patients with essential hypertension. After 7 weeks treatment with ketanserin (mean dose 71 mg/d) there was a significant fail of both systolic and diastolic blood pressure, as compared to placebo, with a peak effect of 19.1/9.1 mmHg lying (P < 0.01/ P < 0.01), and 16.5/11.3 mmHg standing (P < 0.01/P < 0.01); twice daily dosage appeared satisfactory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

1986
1986
1995
1995

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…For the 12 other patients, the effects of ketanserin treatment on blood pressure were similar in the supine and erect positions. Heart rate was reduced on ketanserin treatment compared with placebo, in agreement with previous findings in younger patients [7,8]. Twenty-four hour ECG tapes showed that abnormal rhythms were common in these patients.…”
Section: Resultssupporting
confidence: 90%
“…For the 12 other patients, the effects of ketanserin treatment on blood pressure were similar in the supine and erect positions. Heart rate was reduced on ketanserin treatment compared with placebo, in agreement with previous findings in younger patients [7,8]. Twenty-four hour ECG tapes showed that abnormal rhythms were common in these patients.…”
Section: Resultssupporting
confidence: 90%
“…The therapeutic dose of 2 0 4 0 mg twice daily controlled blood pressure over 24 hr, as measured intra-arterially ( Fig. 2) and by ambulatory monitoring Andren et al, 1983;Cameron and Ramsay, 1985;De Lorenzo et al, 1986;Hedner et al, 1983Hedner et al, , 1985Strano et al, 1986;Waal-Manning et al, 1984Wing et al, 1984;and unpublished data].…”
Section: Chronic Antihypertensive and Hemodynamic Effects Comparison mentioning
confidence: 91%
“…22). Ketanserin does not reduce blood pressure below the normal level in normotensive individuals (for published data see 1, 4,26,57,66,289,291).…”
Section: Comparison With Placebo and Optimal Dosementioning
confidence: 99%